2016
DOI: 10.1177/1079063214556357
|View full text |Cite
|
Sign up to set email alerts
|

Executive Dysfunction Predicts Delinquency But Not Characteristics of Sexual Aggression Among Adolescent Sexual Offenders

Abstract: Our aim in this study was to evaluate executive function and its relationship to delinquency and sexual crime in adolescents incarcerated for sexual crimes. Based on self-report data, 196 male adolescent sexual offenders from a Midwest state reported high rates of executive dysfunction. Although such deficits did not relate to the number of victims of sexual abuse, severity, or degree of force used in commission of the sexual crimes, poor executive function was significantly predictive of both general delinque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…Twenty-two out of the 48 studies in this scoping review reported the psychometric characteristics of the BRIEF. Apart from two studies (Burton et al, 2016; Owens et al, 2016) where the reported sub-scale internal consistency of the BRIEF was below the recommended cut-off standard of 0.70 (Cicchetti, 1994), all the other reported reliabilities (Cronbach alphas, inter-rater and test-retest) ranged from good to excellent. BRIEF appears to be a valid measure of EF in terms of its construct, concurrent, and discriminant validity.…”
Section: Discussionmentioning
confidence: 95%
“…Twenty-two out of the 48 studies in this scoping review reported the psychometric characteristics of the BRIEF. Apart from two studies (Burton et al, 2016; Owens et al, 2016) where the reported sub-scale internal consistency of the BRIEF was below the recommended cut-off standard of 0.70 (Cicchetti, 1994), all the other reported reliabilities (Cronbach alphas, inter-rater and test-retest) ranged from good to excellent. BRIEF appears to be a valid measure of EF in terms of its construct, concurrent, and discriminant validity.…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that perhaps these deficits could contribute to offense patterns differentially such that youth who only commit sexual crimes may not be as astute in assessing consequences or the impact of behavior. Some of these characteristics have been previously studied, and although researchers have documented disinhibitions and limited behavioral and emotional regulation among youth who commit sexual crimes (Burton et al, 2016; Miner, 2002; Stinson et al, 2008), there is inconclusive evidence underlying how such deficits actually predict criminal behavior. Further prospective research needs to evaluate these executive functioning capacities in relation to the criminal behavior perpetrated by the youth, as some offenses may require more planning, thought, and strategy, whereas others may be linked to more impulsivity; such distinctions may also depend on certain trait characteristics of offenders (Lawing, Frick, & Cruise, 2010; van Wijk et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence to support a relationship between executive function deficits and youth criminality (Burton, Demuynck, & Yoder, 2016; Hoaken et al, 2007; Kelly et al, 2002; Morais et al, 2016; Zou et al, 2013). Relative to general population youth, juvenile offenders show higher rates of impairments in executive functioning including lower intellectual capacity exhibited by lower IQ scores and inhibited abilities related to executive functioning (Zou et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Only eight published neuropsychological studies are currently available for juveniles who have sexually offended (JSO) (Burton, Demuynck, & Yoder, 2016; Gillis, 2005; Kelly, Richardson, Hunter, & Knapp, 2002; Morais, Joyal, Alexander, Fix, & Burkhart, 2016; Salat, 2009; Tarter, Hegedus, Alterman, & Katz-Garris, 1983; Veneziano, Veneziano, Legrand, & Richards, 2004; Wahlberg, Kennedy, & Simpson, 2003). As expected, JSO were found to have impairments in executive functions when compared with adolescents recruited from the general population (Gillis, 2005) and with adolescents matched for socioeconomic status (Kelly et al, 2002).…”
Section: Introductionmentioning
confidence: 99%